A Case of Chronic Wernicke’s Encephalopathy: A Neuropsychological Study - Oudman, Erik; Van der Stigchel, Stefan; Postma, Albert; Wijnia, Jan W.; Nijboer, Tanja C. W. (Frontiers in Psychiatry, 2014)
A 54-year old woman was referred to our Korsakoff Center because of extensive cognitive problems following acute Wernicke's Encephalopathy (WE). She had a relatively short history of alcohol abuse and was found lying on the floor in her home by her son. After five days without treatment she was diagnosed with WE in a general hospital. During the course of the disease minimal change to the acute situation occurred, with chronic confusion, attention deficits and incoherent behavior symptoms most notable unlike classical Korsakoff's Syndrome (KS). Neuropsychological assessment after four and sixteen months after admission to the hospital revealed global cognitive decline, with striking impairments in attentional, executive and memory functions. The present case study suggests that the state of confusion and the neuropsychological symptoms in WE can become chronic in case of very late treatment. We therefore recommend that confused alcoholics should receive appropriate parenteral thiamine according to the current clinical standards.